Direct Mechanical Intervention Versus Bridging Therapy in Stroke Patients Eligible for Intravenous Thrombolysis: A Pooled Analysis of 2 Registries. Issue 12 (December 2017) - Bellwald, Sebastian; Weber, Ralph; Dobrocky, Tomas; Nordmeyer, Hannes; Jung, Simon; Hadisurya, Jeffrie; Mordasini, Pasquale; Mono, Marie-Luise; Stracke, Christian P.; Sarikaya, Hakan; Bernasconi, Corrado; Berger, Klaus; et al.
Abstract : Background and Purpose—: Randomized controlled trials have shown that mechanical thrombectomy (MT) plus best medical treatment improves outcome in stroke patients with large-vessel occlusion in the anterior circulation. Whether direct MT is equally effective as bridging thrombolysis (intravenous thrombolysis plus MT) in intravenous thrombolysis eligible patients remains unclear. Methods—: We compared clinical and radiological outcomes at 3 months in 249 bridging patients with 111 patients receiving direct MT for large-vessel occlusion anterior circulation stroke from 2 prospective registries (study period Essen: June 2012 to August 2013, Bern February 2009 to August 2014). We matched all patients from the direct MT group who would have qualified for intravenous thrombolysis with controls from the bridging group, using multivariate and propensity score methods. Subgroup analyses for internal carotid artery occlusions were performed. Results—: Baseline characteristics did not differ between the direct MT group and bridging cohort, except for higher rates of coronary heart disease ( P =0.029) and shorter intervals from onset to endovascular therapy ( P <0.001) in the MT group. Functional outcome, mortality, and intracerebral hemorrhage did not differ, neither in univariate nor after multivariate and propensity score matching. However, in patients with internal carotid artery occlusion, mortality in the direct cohort was significantly lower. Conclusions—: In this matched-pair analysis, there was no difference in outcome in patients with large-vessel occlusion anterior circulation stroke treated with direct MT compared with those treated with bridging thrombolysis; however, mortality in patients with internal carotid artery occlusion treated with direct MT was significantly lower than after bridging thrombolysis. Randomized trials comparing direct MT with bridging therapy are needed. Abstract : Supplemental Digital Content is available in the text.